Jane Huang, en colaboración con Michael Wurmbrandt (traductores), The Primordial Breath; An Ancient Chinese Way of Prolonging Life Through Breath Control, Original Books, Torrance, CA, 1987, vol. 1, pp. 169; vol. 2, en prensa. - Maeth Ch., Russell (Estudios de Asia y África, 1989)
-